Consumerism in prenatal diagnosis: a challenge for ethical guidelines - Henn, Wolfram (Journal of medical ethics, 2000)
The ethical guidelines for prenatal diagnosis proposed by the World Health Organisation (WHO), as well as by national regulations, only refer to paternity and gender of the fetus as unacceptable, disease-unrelated criteria for prenatal selection, as no other such parameters are at hand so far. This perspective is too narrow because research on complex genetic systems such as cognition and ageing is about to provide clinically applicable tests for genetic constituents of potentially desirable properties such as intelligence or longevity which could be misused as parameters for prenatal diagnosis. Moreover, there is an increasing number of prenatally testable genetic traits, such as heritable deafness, which are generally regarded as pathological but desired by some prospective parents and taken into account as parameters for pro-disability selection. To protect prenatal diagnosis from ethically unacceptable genetic consumerism, guidelines must be clarified as soon as possible and updated towards a worldwide restriction of prenatal genetic testing to immediately disease-determining traits.